2016
DOI: 10.1080/15384101.2016.1259039
|View full text |Cite
|
Sign up to set email alerts
|

RAC2-P38 MAPK-dependent NADPH oxidase activity is associated with the resistance of quiescent cells to ionizing radiation

Abstract: Our recent study showed that quiescent G0 cells are more resistant to ionizing radiation than G1 cells; however, the underlying mechanism for this increased radioresistance is unknown. Based on the relatively lower DNA damage induced in G0 cells, we hypothesize that these cells are exposed to less oxidative stress during exposure. As a catalytic subunit of NADPH oxidase, Ras-related C3 botulinum toxin substrate 2 (RAC2) may be involved in the cellular response to ionizing radiation. Here, we show that RAC2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Increasing evidence supports that mitogen-activated protein kinases (MAPKs) mediate apoptosis and autophagy in response to chemotherapy. 19 , 20 MAPKs are key players in the regulation of cell proliferation and cancer development. Activation of p38 MAPK could augment the processes of apoptosis and autophagy.…”
mentioning
confidence: 99%
“…Increasing evidence supports that mitogen-activated protein kinases (MAPKs) mediate apoptosis and autophagy in response to chemotherapy. 19 , 20 MAPKs are key players in the regulation of cell proliferation and cancer development. Activation of p38 MAPK could augment the processes of apoptosis and autophagy.…”
mentioning
confidence: 99%
“…A study showed that baseline MAPK signaling activity conferred intrinsic radioresistance to KRAS-mutant colorectal carcinoma cells by rapid up-regulation of hnRNP K ( Eder et al, 2017 ). Moreover, quiescent G0 cells were found to be more resistant to ionizing radiation than G1 cells because P38 MAPK , phosphorylated P38 MAPK , and RAC2 were regulated in mutual feedback and negative feedback regulatory pathways, leading to the radioresistance of G0 cells ( Pei et al, 2017 ). Interestingly, RPS6KA5 , RPS6KA6 , CRKL , RAP1A , FASLG , and MAPK8 were found in both MAPK and neurotrophin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of P38 MAPK enhanced cellular radioresistance. However, excessive ROS production led to P38 MAPK dephosphorylation, suggesting that the ROS/RAC2/P38 MAPK feedback loop generates quiescent cells more resistant to ionizing radiation (IR) [13]. These findings reveal a new paradigm for understanding radioresistance of G0 cells and support the potential application of RAC2 inhibitors as radiation protectants.…”
Section: Strategies To Improve Radioresistance Of Quiescent Tumor Cellsmentioning
confidence: 91%
“…Although the protected state is favorable for long-term maintenance of the quiescent state, activation of these pathways in tumor cells may play a crucial role in higher resistance to conventional cancer therapies that largely target proliferating cells [3,5,11,12]. Quiescent tumor cells are considered significantly less radio/ chemosensitive with a greater repair capacity than cycling cells [11,13,14]. Resistance of G0 cells from breast, pancreatic, ovarian tumors and squamous cell carcinomas to traditional therapeutic patterns has been reported [3,15].…”
Section: Quiescent Tumor Cells Represent a Clinical Problemmentioning
confidence: 99%
See 1 more Smart Citation